Model Pembelajaran Al-Qur’an Metode Ummi: Analisis Goodwill Manajemen dan Mastery Learning di SMP Islam Cikal Harapan 1 BSD - Muhamad Lutfil Ansori (Journal of Citizenship, 2026)
The results of the study indicate that the implementation of the Ummi method at SMP Islam Cikal Harapan 1 BSD is not only focused on technical aspects of understanding Qur’anic recitation, but is also professionally managed through a system that builds goodwill, such as supportive leadership, efficient communication between teachers and parents, and consistency in improving teaching quality. In addition, the learning strategies applied are highly aligned with the principles of mastery learning, which include stages of competency mastery, formative evaluation, remedial programs, and instruction tailored to students’ learning pace. The integration of these two approaches yields positive outcomes in improving the quality of learning, enhancing students’ learning motivation, and strengthening the public image of SMP Islam Cikal Harapan 1 BSD. Therefore, the Qur’anic learning model using the Ummi method that integrates goodwill management values and the mastery learning approach can serve as an effective and sustainable educational model within the context of Islamic education. Keywords: Ummi Method, Qur’anic Learning, Goodwill Management, Mastery Learning, SMP Islam Cikal Harapan 1 BSD.